Metagenomic Insight into the Effect of Probiotics on Nitrogen Cycle in the Coilia nasus Aquaculture Pond Water - Qi Mang; Jun Gao; Quanjie Li; Yi Sun; Gangchun Xu; Pao Xu (Microorganisms, 2024)
Recently, probiotics have been widely applied for the in situ remediation of aquatic water. Numerous studies have proved that probiotics can regulate water quality by improving the microbial community. Nitrogen cycling, induced by microorganisms, is a crucial process for maintaining the balance of the aquatic ecosystem. Nevertheless, the underlying mechanisms by which probiotics enhance water quality in aquatic systems remain poorly understood. To explore the water quality indicators and their correlation with nitrogen cycling-related functional genes, metagenomic analysis of element cycling was performed to identify nitrogen cycling-related functional genes in Coilia nasus aquatic water between the control group (C) and the groups supplemented with probiotics in feed (PF) or water (PW). The results showed that adding probiotics to the aquatic water could reduce the concentrations of ammonia nitrogen (NH4+-N), nitrite (NO2−-N), and total nitrogen (TN) in the water. Community structure analysis revealed that the relative abundance of Verrucomicrobiota was increased from 30 d to 120 d (2.61% to 6.35%) in the PW group, while the relative abundance of Cyanobacteria was decreased from 30 d to 120 d (5.66% to 1.77%). We constructed a nitrogen cycling pathway diagram for C. nasus aquaculture ponds. The nitrogen cycle functional analysis showed that adding probiotics to the water could increase the relative abundance of the amoC_B and hao (Nitrification pathways) and the nirS and nosZ (Denitrification pathways). Correlation analysis revealed that NH4+-N was significantly negatively correlated with Limnohabitans, Sediminibacterium, and Algoriphagus, while NO2−-N was significantly negatively correlated with Roseomonas and Rubrivivax. Our study demonstrated that adding probiotics to the water can promote nitrogen element conversion and migration, facilitate nitrogen cycling, benefit ecological environment protection, and remove nitrogen-containing compounds in aquaculture systems by altering the relative abundance of nitrogen cycling-related functional genes and microorganisms.